Faculty retention in regional medical schools in Iran: a qualitative content analysis - Maria Shaterjalali; Yousef Gholampoor; Ali Khani Jeihooni; Yaser Mansoori; Reza Homayounfar; Elham Ehrampoush; Shahnaz Karimi (BMC Medical Education, 2021)
Abstract Background and purpose Recruitment and retention of competent faculty members are important in maintaining and improving the quality of education and research performance of universities. The aim of the present study was to find out the faculty members’ views, experiences, and attitudes to identify the reasons for faculty attrition and retention in regional medical schools in Iran. Methods In this qualitative study, we used a content analysis method. The participants included 12 faculty members who had been transferred to type I universities, four faculty members who had applied for transfer, four with more than 10 years of experience and working in the type 3 universities with no intention to be transferred. Data were collected using semi-structured interviews, which were conducted either face-to-face or via phone calls. The interview was developed for this study (Supplementary file). To measure the trustworthiness of the data, we evaluated four components of credibility, transferability, dependability, and conformability, as proposed by Lincoln and Guba. Results The findings were classified into three categories and 14 subcategories. The first category was “retention facilitators” including four subcategories of facilitated communication, proximity to major universities, gaining experience, and support by authorities. The second category was “retention threats” including six subcategories of social infrastructure, individual dimension, occupation dimension, economic dimension, sense of respect, and executive management. The third category was “retention strategies” which included four subcategories of recruitment and promotion processes, inter-university collaboration with type I universities, facilitation of the scientific growth, and fulfilment of the safety needs. Conclusion Several factors play a role in the faculty members’ retention in regional medical schools in Iran. Authorities can create a more positive environment by devising a suitable reward system, supporting academic activities, and increasing the level of faculty autonomy practically to develop a sense of belonging among them and reduce the intention to be transferred among their human resources.